THE STUDY ON THE POSSIBILITIES FOR ESTABLISHING FTA BETWEEN MONGOLIA AND THE EAEU: ANALYSIS OF NON-TARIFF MEASURES - U.Nomintsetseg (Journal of Business and Innovation (Бизнес & Инноваци), 2023)
Mongolia has recently concluded an Economic Partnership Agreement (EPA) with Japan in 2016; however the country further seeks to align with integration in other regions in order to accelerate its economic and social development. One of those efforts is that Mongolia requested to launch a joint study on possible FTA with the Eurasian Economic Union (EAEU). There have been number of studies aim to undertake quantitative analysis on the formation of a FTA between Mongolia and the EAEU. However, there is still lack of analysis on the qualitative side, namely non-tariff measures of the EAEU. Therefore, this study tries to shed some light on the non-tariff barriers when two sides forming possible FTA in the near future.